Carterʼs initiative to withdraw American troops from South Korea in 1976–1980: reasons for failure - Sadakov, Denis A. (Journal of the Belarusian State University. History, 2024)
The process of implementation of one of the most important points of the election programme of USA president J. Carter, concerning the gradual withdrawal of USA ground forces and tactical nuclear weapons from the territory of the Korean Peninsula, is considered. This initiative was largely due to scandals related to the activities of the Korean Central Intelligence Agency in the USA, cases of bribery of American congressmen by South Koreans, and the growing negative attitude of Americans towards the authoritarian regime of the President of the Republic of Korea, Park Chung Hee. The plan prepared by the presidential administration for the implementation of election promises is analysed. It is noted that the withdraw troops from the Korean Peninsula was supposed to be carried out in phases over four or five years. It was not supposed to significantly change the military balance in the region. It is indicated that an obstacle to the implementation of the plan was the position of the Congress of the USA, which did not approve the package of compensation measures agreed with the South Koreans. The reason for the resistance of congressmen was both the general inertia of American foreign policy and weak domestic political preparation for the sharp step of the presidential administration. Despite this, J. Carter continued to look for opportunities to fulfill his election promises. It is concluded that the result of this initiative was only a banal exchange of abandoning plans to withdraw American troops from the peninsula for a limited softening of the orders of the South Korean dictatorship.